1999
DOI: 10.1038/sj.jhh.1000743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of candesartan cilexetil on oxidative state and renal function in 5/6 nephrectomized rats

Abstract: We have investigated the influence of a novel angiotensin II type 1 receptor antagonist, candesartan cilexetil, on the oxidative state of renal tissue and renal function in 5/6 nephrectomized rats, and compared its effects with those of an angiotensin-converting enzyme inhibitor, enalapril. Candesartan cilexetil (1 and 5 mg/kg per day), enalapril (5 mg/kg per day) and vehicle were orally administered once daily for 16 weeks after 5/6 nephrectomy. There was a marked degree of proteinuria evident prior to treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
4
13
1
Order By: Relevance
“…In our study, enalapril (5 mg/kg per day) and vehicle were orally administered once daily by gastric gavage for 16 weeks after 5/6 nephrectomy [3]. Our results showed that lipid peroxides assessed by malondialdehyde content in the homogenate from the renal cortex significantly increased in the nephrectomized rats.…”
mentioning
confidence: 61%
“…In our study, enalapril (5 mg/kg per day) and vehicle were orally administered once daily by gastric gavage for 16 weeks after 5/6 nephrectomy [3]. Our results showed that lipid peroxides assessed by malondialdehyde content in the homogenate from the renal cortex significantly increased in the nephrectomized rats.…”
mentioning
confidence: 61%
“…The other half (n = 6/group) were provided with plain drinking water for 7 days. The dose of CAN was similar to oral doses used by other investigators [911]. …”
Section: Methodsmentioning
confidence: 85%
“…Rats were housed singly in microfilter top, plastic cages with a normal 12:12-h light-dark cycle, according to protocols approved by the Georgetown Animal Care and Use Committee. After 1 wk of baseline BP recording (at ϳ9 wk of age), 8 rats from each body type were randomly assigned to either ground control diet (Purina 5001 Rodent Chow, Purina Mills, St. Louis, MO) solidified in agar with 70% water, or the same base diet with 23.5 mg ground CAN cilexetil (Atacand, AstraZeneca Pharmaceuticals, Wilmington, DE) incorporated per kilogram diet (wet weight) to provide a dose of CAN in the range of 3-5 mg ⅐ kg body wt Ϫ1 ⅐ day Ϫ1 , similar to oral doses used by other investigators (26,34,36). Rats were weighed weekly and fed diets and received water ad libitum for 14 wk.…”
Section: Methodsmentioning
confidence: 96%